Psychological Factors of Myocardial Infarction: Prospects for Clinical and Psychological Research - R. V. Kadyrov; A. S. Elzesser; N. S. Bartkovskaia (Вестник Кемеровского государственного университета, 2020)
This article is a review of empirical studies on the topic of psychological characteristics that contribute to the incidence of myocardial infarction. Such studies are fragmented and deal mostly with the following categories: mental states, patient’s mental processes, symptoms of mental disorders, behavioral strategies, social factors, etc. The research objective was to analyze the results of empirical studies on the myocardial patients' psychological characteristics. The authors identified difficulties and contradictions in the studies. Diagnostic capabilities of type A proved no longer relevant. An analysis of the contradictions in type D studies suggested that longitudinal studies based on a initially healthy people would prove most effective for further research, as well as detailed meta-analyzes of empirical publications. The role of hostility in the genesis of myocardial infarction proved understudied by domestic scientists. As for anxiety in patients with myocardial infarction, it received enough scientific attention; however, researches do not agree about role in the development of myocardial infarction. To reduce psychological risks during cardiovascular diseases, it is necessary to determine what conditions and factors accelerate or inhibit the onset of myocardial infarction when combined with personal anxiety. The authors propose to use the following samples: 1) patients with a risk of a heart attack; 2) patients after a heart attack; 3) patients past rehabilitation period. The findings indicate promising areas for future research for the prevention of myocardial infarction.